Estudo químico e biológico da Remijia amazonica K. Schum. (Rubiaceae) - Souza, Fábio Geraldo de (Botânica, 2025)
The Rubiaceae family is the fourth largest botanical family in terms of total number of species occurring in the tropical regions of the world. Species of the family are rich in secondary metabolites, containing alkaloids, terpenes, iridoids, and other classes that have various biological activities. Despite the wide variety of species, many have not yet been studied, among them the species Remijia amazonica K. Schum. Therefore, this study aimed to conduct a chemical and biological study of R. amazonica. For this purpose, hexane and methanolic extracts were obtained from leaves and branches. The following methodologies were used to determine biological/chemical activities: DPPH and Fe3+/phenanthroline tests for antioxidant activity; broth microdilution to determine the minimum inhibitory concentration (MIC) in antimicrobial activity; and Artemia salina was used to assess toxicity. The isolated substances were identified using spectroscopic methods (1H, 13C, and two-dimensional NMR) combined with mass spectrometry. In the toxicity test against A. salina, the DCM phase showed strong toxicity with a CL50 of 3.6 μg/mL. From the methanolic extract of the leaves, the AcOEt phase showed antioxidant capacity in the DPPH and Fe3+/phenanthroline tests. In the antimicrobial activity evaluation, the hexane extracts showed activity against the microorganisms Aeromonas hydrophila, Citrobacter freundii, and Escherichia coli. The methanolic extracts from the leaves showed activity against Candida tropicalis, Citrobacter freundii, Escherichia coli, and Staphylococcus aureus. After fractionation of the methanolic extract of the leaves, it was possible to isolate three substances, two indole alkaloids, 11-methoxy-3-isorauniticin and 9-methoxy-3-iso-19-epiajmalicin, and one coumarin, scopoletin. The results obtained in this study show the great chemical and biological potential of this species for the isolation of active substances. Keywords: Indole alkaloids, coumarin, Artemia salina, antimicrobial activity, antioxidant activity
Keywords: Alcalóides indólicos; Cumarina; Artemia salina